The Cossidae (Lepidoptera) of Malawi with descriptions of two new species - Yakovlev, Roman V.; Murphy, Raymond J. (Zootaxa, 2013)
An annotated list of Cossidae of Malawi including 30 species from 13 genera and 3 subfamilies is presented for the first time. Two new species are described: Macrocossus grebennikovi Yakovlev, sp. nov. and Strigocossus elephas Yakovlev, sp. nov. Three new synonyms are established: Strigocossus moderatus (Walker, 1856) = Strigocossus leucopteris Houlbert, 1916, syn. nov. = Xyleutes sjoestedti vosseleri Gaede, 1930, syn. nov. and Strigocossus capensis (Walker, 1856) = Azygophleps kilimandjarae Le Cerf, 1914, syn. nov.